Analysis Of Water Requirements For Irrigation Of Green Honey Water Apple (Syzygium aqueum) In Pots - Julia, Hilda; Novita, Aisar; Ketaren, Bunga Raya (Talenta Publisher, 2021)
Plant irrigation water needs are important things to be met so that the plant growth is optimal starting from the vegetative phase to the generative phase. The current hot issue among potted fruit growers is the problem of dropping the ovary (pistil) on the plant. Many factors cause the fall of plant fruit, one of which is lack of water. This certainly needs special attention considering the nature of the water apple plant itself, in this study, especially the green honey water apple, it consumes quite a lot of water every day. To overcome the problem of water shortages in the green honey water apple plant, it is necessary to first know the average plant water requirement in pots through water content analysis in the laboratory at three stages of analysis and calculation of Pot Water Requirements (PWR) and Efficiency Needs Irrigation Water. Average Field Capacity Moisture Content of the potted planting media sample was 49.37%, Air Dry Moisture Content was 24.27 % and PWR 4.36 liters with an efficiency of irrigation water requirement for bulk systems (hand move or portable) of 5, 12-5.81 liters and a drip irrigation system (point source emitter) of 4.84-5.45 liters.